The political transformations in the context of COVID-19 - Salloum, Feras Sadiq (Journal of the Belarusian State University. International Relations, 2021)
Like the fall of the Berlin wall in 1989 and the global economic crisis in 2008, COVID-19 is viewed to be a turning point in the international system. Just as the coronavirus altered the habits of many societies, claimed the lives of thousands, disrupted markets, revealed the efficiency or lack thereof of governments, it may drive into permanent transformations in the world’s political system. The aim of this article is to reveal whether COVID-19 will reshape the current world order. The article focuses on the impact of COVID-19 on international relations. The opinions of various authors, politicians, and journalists on the effects of coronavirus on the world order are described. A reasonable conclusion is drawn about the state of the USA and China and the emergence of a new world order.